Pain associated with fine-needle aspiration biopsy of thyroid nodules - Stangierski, Adam; Ruchała, Marek; Warmuz-Stangierska, Izabela; Głowacka, Maria Danuta; Zdanowska, Joanna; Głowacka-Rębała, Alicja; Rasińska, Renata; Czarnywojtek, Agata (Menopause Review/Przegląd Menopauzalny, 2012)
Introduction : The importance of FNAB tool in the pre-surgical diagnosis. Aim of the study : The aim of this study was to look for patients’ comfort improvement and the best diagnostic conditions as we intended to obtain the real estimation of patient’s pain intensity and the correlation between patient’s hormonal status, age, sex, nodule type with the level of pain sensation. Material and methods : The research was carried out in a group of 75 patients of the Clinic of Endocrinology, Metabolism and Internal Medicine. The inclusion criteria at a thyroid outpatient clinic were as follows: the thyroid nodules that required an US-FNAB were 10 mm or larger in the maximum diameter and the locations of the thyroid nodules were intraglandular and were relatively central in thyroid. The main study method was the pain scale measuring patient’s pain intensity, based on a self-report. Results : The obtained scores showed moderate pain as dominant in the study group and no statistically significant correlation between the intensity of pain, age, sex, density of the nodules (calcifications), initial diagnosis and hormonal status of the patient. Conclusions: The use of different anesthetics during thyroid FNAB has already been reported as ineffective, thus alternative methods of decreasing pain during biopsy should be considered.